Statistical Data of Differentiation of Tourist Expenses - Nino Abesadze; Marine Mindorashvili; Nino Paresashvili (Фінансово-кредитна діяльність: проблеми теорії та практики, 2016)
Purpose of the Article. The main purpose of the article is to make complex statistical analysis of tourist expenses of foreign visitors.